Prophylactic antibiotics before cord clamping in cesarean delivery: a systematic review. (30th December 2017) - Bollig, Claudia; Nothacker, Monika; Lehane, Cornelius; Motschall, Edith; Lang, Britta; Meerpohl, Joerg J.; Schmucker, Christine M.
Abstract: Introduction: The number of clinical trials investigating the optimal timing of prophylactic antibiotics in cesarean section has increased rapidly over the last few years. We conducted a systematic review to inform up‐to‐date evidence‐based guidelines to prevent postpartum infectious morbidity in the mother and rule out any safety issues related to antepartum antibiotic exposure in infants. Material and methods: Four bibliographic databases were searched for published reports of trials. Ongoing or unpublished studies were searched in Clinicaltrials.gov and the World Health Organization registry platform. Randomized controlled trials comparing antibiotic prophylaxis before and after cord clamping in cesarean section were eligible. Maternal and neonatal outcomes were assessed, and certainty of evidence graded. Results: In total, 18 randomized controlled trials met the inclusion criteria. Those women who received antibiotics preoperatively were 28% (relative risk 0.72, 95% confidence interval 0.56–0.92, nine studies, 4342 women, high quality of evidence) less likely to show infectious morbidity as compared with those who received antibiotics after cord clamping. The risk of endomyometritis and/or endometritis was reduced by 43% (relative risk 0.57, 95% confidence interval 0.40–0.82, 13 studies, 6250 women, high quality of evidence) and the risk of wound infection by 38% (relative risk 0.62, 95% confidence interval 0.47–0.81, 14 studies, 6450 women, high quality of evidence) in those who received antibiotics preoperatively as compared to those who received antibiotics after cord clamping. For other maternal infections no significant differences were identified. The risk for neonatal outcomes, such as deaths attributed to infection, sepsis, neonatal antibiotic treatment, intensive care unit admission or antibiotic‐related adverse events, was not found to be different, either clinically or statistically, when antibiotics were given before or after cord clamping (moderate to low quality of evidence). Conclusions: The evidence in favor of prophylactic antibiotic administration before, in comparison with after, cord clamping for major maternal infections was of high quality, meaning that further research would be unlikely to change the confidence in these findings. However, we recommend additional research reflecting the precision of the effect estimates for neonatal outcomes.